2021
DOI: 10.34197/ats-scholar.2020-0034oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Novel Multiinstitutional Curriculum on Critical Care Fellow Ventilator Knowledge

Abstract: Background: Management of mechanical ventilation (MV) is a curricular milestone for trainees in pulmonary critical care medicine (PCCM) and critical care medicine (CCM) fellowships. Though recognition of ventilator waveform abnormalities that could result in patient complications is an important part of management, it is unclear how well fellows recognize these abnormalities. Objective: To study proficiency of ventilator waveform analysis among first-year fellows enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…We found that performance on important clinical topics was variable. There was a high percentage of error for the item that evaluates recognition of patient–ventilator asynchrony, in agreement with previous studies emphasizing the difficulty health professionals have in recognizing and managing asynchrony ( 31 , 32 ). Considering that asynchrony is a common phenomenon and is associated with extubation failure ( 33 ) and mortality ( 34 , 35 ), this finding underscores the need for intentional training ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that performance on important clinical topics was variable. There was a high percentage of error for the item that evaluates recognition of patient–ventilator asynchrony, in agreement with previous studies emphasizing the difficulty health professionals have in recognizing and managing asynchrony ( 31 , 32 ). Considering that asynchrony is a common phenomenon and is associated with extubation failure ( 33 ) and mortality ( 34 , 35 ), this finding underscores the need for intentional training ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…There was a high percentage of error for the item that evaluates recognition of patient–ventilator asynchrony, in agreement with previous studies emphasizing the difficulty health professionals have in recognizing and managing asynchrony ( 31 , 32 ). Considering that asynchrony is a common phenomenon and is associated with extubation failure ( 33 ) and mortality ( 34 , 35 ), this finding underscores the need for intentional training ( 32 ). The item requiring participants to measure respiratory system resistance also had a high percentage of error, possibly reflecting a lack in familiarity with performing such measurements at the bedside.…”
Section: Discussionsupporting
confidence: 90%
“…It is worth noting that these postcurriculum improvements are in line with previous work detailing trainings of similar content and in similar settings. In one recent study in the United States, a 3-day, multi-institutional, ventilator waveform training showed improvement in post-training knowledge examination of 37% ( 27 ). Another study of short-term, multimodal, advanced cardiac life support training, which occurred in Haiti, demonstrated postcurriculum knowledge improvement of 22% after one training ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, optimizing such techniques and strategies is an acquired skill that takes time to develop, let alone master. Even still, it has been shown that, while most rst-year fellows in Pulmonary and Critical Care are not vent-savvy when starting fellowship, this skill is adequately acquired with training and practice when provided with standardized equipment [10]. Furthermore, recent analysis of disaster-readiness has shown that skilled intensivists and respiratory therapists continue to be a bottleneck in providing care during a surge situation such as the rst wave of the COVID-19 pandemic [11].…”
mentioning
confidence: 99%